World Development Report 2002 (Overview) Building Institutions for Markets. (Washington, D.C. The World Bank, 2001)
Abstract: Markets should give incentives to engage in wider trade, forge the ability to use resources, and skills fully, and provide the opportunity to increase incomes, and accumulate assets. Despite underlying problems, many people in both developed , and developing countries do engage in productive, and rewarding market activity, for income from market participation is the key to economic growth for nations, and to reducing poverty for individuals. This report is about enhancing opportunities for poor people in markets, and empower them, provided regulatory frameworks, law enforcement, and organizational promotion accompany market transactions. Hence, building institutions that support the development of markets is the primary focus of this report, analyzing what institutions do to promote growth, and facilitate access, and suggesting how to build effective institutions. In understanding what drives institutional change, the report emphasizes the importance of history, highlighting the need to ensure effective institutions through: a design that complements existing institutions, human capabilities, and available technologies; innovations to identify both institutions that work, and those that do not; communities of market players connected through open information, and trade; and, the promotion of competition among jurisdictions, firms, and individuals. This overview is a presage to the World Development Report 2002, which shows that institutional strength ensures stable, and inclusive growth.
10.1596/0-8213-5016-1.
Additional physical form: Print Version:9780821350164.
Keywords: Access to Finance; Debt Markets; E-Business.; Economic Theory and Research; Finance and Financial Sector Development; Labor Policies; Macroeconomics and Economic Growth; Private Sector Development; Social Protections and Labor